2018
DOI: 10.1002/app.46441
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mechanical properties of polypropylene separator in liquid electrolytes for lithium‐ion batteries

Abstract: Knowledge of the mechanical behaviors of polymeric separators immersed in liquid electrolytes is of great significance for predicting the long‐term performance of lithium batteries with high performance and safety. In terms of tensile tests, heating shrinkage, and dynamic mechanical analysis as well as the essential work of fracture method, the study reported here encompasses a systematic investigation of the mechanical properties of a typical commercial polypropylene separator in mixtures of ethylene carbonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…Therefore, it can be summarized here that the treatments by an oil bath can significantly improve the toughness in the TD and the puncture resistance of the separator with only slight drops of the yield strength. To understand fully, the measurement of the essential work of fraction (EWF) has been performed according to previous elegant studies. , The EWF measurement can provide detailed information concerning the fracture resistance behavior of the separators with and without the white oil treatment. The results provided in Figure S1 and Table S1 in the Supporting Information section revealed that after the white oil treatment, the load–displacement curves for the DEN-T specimens of SWO-2H are quite different from that of SWO-0, to be more exact, a longer displacement before the total failure and the lower loading force of SWO-2H can be seen compared with that of SWO-0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be summarized here that the treatments by an oil bath can significantly improve the toughness in the TD and the puncture resistance of the separator with only slight drops of the yield strength. To understand fully, the measurement of the essential work of fraction (EWF) has been performed according to previous elegant studies. , The EWF measurement can provide detailed information concerning the fracture resistance behavior of the separators with and without the white oil treatment. The results provided in Figure S1 and Table S1 in the Supporting Information section revealed that after the white oil treatment, the load–displacement curves for the DEN-T specimens of SWO-2H are quite different from that of SWO-0, to be more exact, a longer displacement before the total failure and the lower loading force of SWO-2H can be seen compared with that of SWO-0.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important components of the LIB interior is the polymer separator, which is made of polyolefin such as polyethylene (PE) or polypropylene (PP). The manufacturing processes, to be specific, dry and wet , processes, bring significant effects on the mechanical properties of the separators. The PP separators manufactured via a dry process is one of the most successfully developed commercial polymer separators, featured of highly uniform and small-sized micropores, excellent permeability, high electrochemical properties and relatively low manufacturing costs . It is highly anisotropic in the machine direction (MD) and the transverse direction (TD), that is to say, it exhibits high tensile strength and medium elongation at break in the MD, while very low elongation at break in the TD (even less than 15%), which greatly restricts its resistance to the penetration of the lithium dendrites. , Its enhancement, however, can hardly be evidently elevated as far as we have observed up to date.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [112] revealed the influencing factors of tensile strength for PP separators in the wetting condition. They proposed that the tensile properties of polymeric separators appear to be a function of loading rate and the relation between relaxation time and strain rate.…”
Section: Mechanical Behavior Issuementioning
confidence: 99%
“…Many reports have conducted investigation mechanical properties of PP separator submersed in air (or vacuum), water, dimethyl carbonate (DMC), and integrated electrolyte [1.1 M LiPF6 in ethylene carbonate (EC)/dimethyl carbonate (DMC) = 1/1 by volume (1.1 M LiPF6 in EC/DMC)] from experiments and molecular simulation . The effect of temperature has also studied and found to take negative influence . These studies indicate that electrolyte has a certain influence on the weakening, swelling, and softening of PP separators, causing damage on materials and structures.…”
Section: Introductionmentioning
confidence: 99%